Symbiotic Growth of a Thermophilic Sulfide-Oxidizing Photoautotroph and an Elemental Sulfur-Disproportionating Chemolithoautotroph and Cooperative Dissimilatory Oxidation of Sulfide to Sulfate - Kawai, Shigeru; Kamiya, Naoki; Matsuura, Katsumi; Haruta, Shin (Frontiers in Microbiology, 2019)
A thermophilic filamentous anoxygenic photosynthetic bacterium, Chloroflexus aggregans, is widely distributed in neutral to slightly alkaline hot springs. Sulfide has been suggested as an electron donor for autotrophic growth in microbial mats dominated with C. aggregans, but remarkable photoautotrophic growth of isolated C. aggregans has not been observed with sulfide as the sole electron source. From the idea that sulfide is oxidized to elemental sulfur by C. aggregans and the accumulation of elemental sulfur may have an inhibitory effect for the growth, the effects of an elemental sulfur-disproportionating bacterium was examined on the autotrophic growth of C. aggregans, strain NA9-6, isolated from Nakabusa hot spring. A sulfur-disproportionating bacterium, Caldimicrobium thiodismutans strain TF1, also isolated from Nakabusa hot spring was co-cultured with C. aggregans. C. aggregans and C. thiodismutans was successfully co-cultured in a medium containing thiosulfate as the sole electron source and bicarbonate as the sole carbon source. Quantitative conversion of thiosulfate to sulfate and a small transient accumulation of sulfide was observed in the co-culture. Then the electron source of the established co-culture was changed from thiosulfate to sulfide, and the growth of C. aggregans and C. thiodismutans was successfully observed with sulfide as the sole electron donor for the autotrophic growth of the co-culture. During the cultivation in the light, simultaneous consumption and accumulation of sulfide and sulfate, respectively, were observed, accompanied with the increase of cellular DNAs of both species. C. thiodismutans likely works as an elemental sulfur scavenger for C. aggregans, and C. aggregans seems to work as a sulfide scavenger for C. thiodismutans. These results suggest that C. aggregans grows autotrophically with sulfide as the electron donor in the co-culture with C. thiodismutans, and the consumption of elemental sulfur by C. thiodismutans enabled the continuous growth of the C. aggregans in the symbiotic system. This study shows a novel symbiotic relationship between a sulfide-oxidizing photoautotroph and an elemental sulfur-disproportionating chemolithoautotroph via cooperative dissimilatory sulfide oxidation to sulfate.